Some remarks on tonal systems in Carlos Vega's "cancioneros" at 45 years from the publication of his Panorama de la música popular argentina (Revista Argentina de Musicología, 2016)
Based upon recent researches on tonal systems and through a comparative analysis of medieval European, Spanish popular and Argentine folk melodies, this paper purports the underlying presence of the medieval modal system in some Argentine folk repertoires. Some of Carlos Vega's statements regarding his classification of heptatonic "cancioneros" in his widely known Panorama de la música popular argentina are examined under this light and a revaluation of some of the foundations on which that work is grounded is proposed.